How to start a fire [compact disc, unabridged] - Lutz, Lisa (Blackstone Audio, Inc., 2015)
When UC Santa Cruz roommates Anna and Kate find passed-out Georgianna Leoni on a lawn one night, they wheel her to their dorm in a shopping cart. Twenty years later, they gather around a campfire on the lawn of a New England mansion. What happens in between--the web of wild adventures, unspoken jealousies, and sudden tragedies that alter the course of their lives--is charted with sharp wit and aching sadness in this meticulously constructed novel. Anna, the de facto leader, is fearless and restless--moving fast to stay one step ahead of her demons. Quirky, contemplative Kate is a natural sidekick but a terrible wingman. And then there's George: the most desired woman in any room, and the one most likely to leave with the worst man. How to Start a Fire pulls us deep into Anna, Kate, and George's complicated bond and pays homage to the abiding, irrational love we share with the family we choose.